Smartphone for physics practicum in momentum and impulse - Ade Yeti Nuryantini; Rizki Zakwandi; Muhamad Ari Ariayuda (Universitas PGRI Kanjuruhan Malang, 2023)
Practicum is an important part of Physics learning that cannot be ignored even in distance learning. Obstacles of practicum facilities faced by students can be overcome by using sensor on smartphones as a measuring tool. In this study, the use of the accelerometer sensor on a smartphone has been carried out to analyze the concept of momentum and impulse through the collision of two toy cars. Two toy cars A and B with smartphones attached have their respective masses of m1 0.31345 kg and m2 0.32116 kg. Car A was idle and car B was moved until it collided car A. In the event of a collision, the accelerometer sensor recorded acceleration data (a) versus time (t). Data (a) versus time (t) was represented in the form of a curve. Next, the data were analyzed. From the graph obtained data t1 =1.237 seconds, when car B started to exert a contact force on car A. The contact time between cars was Ã¯Ââ€žt = 0.025 seconds. The maximum acceleration experienced by car A during a collision was a = 27.919 m/s2. From the area of the curve (a) vs (t) the impulse value was 0.1217 (N. sec) which is also the value of the change in momentum of car A, with car A's speed after the collision of 0.427 m/s. Thus, the accelerometer sensor on a smartphone can be used to assist students in finding important concepts through practical activities. The use of the accelerometer sensor is expected to help students to facilitate understanding the concepts of momentum and impulse.